Soil and water relations in mangrove ecosystems in Guyana - Dookie, Sabrina; Jaikishun, Sirpaul; Ansari, Abdullah Adil (Geology, ecology, and landscapes, 2024)
In mangrove forests, one of the most noticeable characteristics is the unique interplay between soil and water, which facilitates the movement of nutrients and sediments throughout their ecosystems. In this study, comparisons were made between the physicochemical characteristics of soil (pH, EA, OC, EC, N, P, K, Mg, Ca, S, Fe, Zn, Cu, and Mn) and water (pH, temperature, and electrical conductivity) found in natural, degraded, and restored mangrove ecosystems along the coastline of Guyana. Sampling was done using a Random Block Design (RBD) in six study sites for six months. This study revealed that there were no significant variations in most of the physicochemical parameters found in soil and water within ecosystem type or season. However, notable differences were seen in the pH of water (6.45-7.88), as well as Fe (0.60-21.62 ppm, p < 0.05) and Mg (610-3944.67 ppm, p < 0.05) concentrations of soil within the three types of ecosystems. Seasonal differences were also evident in S, N, P, K, and Cu concentrations found within the mangrove soils. In both seasons, positive correlation findings (p < 0.05, R > 0.75) showed higher associations between soil physicochemical properties concerning ecosystem types,  when compared to water parameters.